Hadronic contribution to the muon g − 2: Theoretical challenges with the MUonE experiment - Piccinini Fulvio (EPJ Web of Conferences)
After briefly reviewing the present status on the theoretical predictions for the hadronic contribution to the muon anomalous magnetic moment, the MUonE approach is introduced, with a discussion on the challenges for the needed theoretical predictions.